Identifikasi Titik Kritis Kehalalan Bahan Hewani dan Produk Turunan Hewan - Jumiono, Aji (Universitas Djuanda, 2022)
The halalness of processed food products is largely determined by the halalness of the materials used in the manufacturing process. Foodstuffs of animal origin and their derivative products are very critical for their halal status. Various processed animal-derived products such as meat, bone, skin, blood, fur/hair and offal can be processed into various products. The use of a decision tree on the status of halal can be used to facilitate the identification of critical points for the halalness of animal-derived products. An understanding of types of halal animals, slaughter methods according to Islamic law and the potential for contamination with unclean or unclean materials is the main focus of this article to provide guidance in ensuring animal-derived products meet halal criteria. A deeper understanding of the halal aspects of animal-derived products is expected to contribute to producing products that meet halal criteria.